The Utilization Of Geography Learning Media At High School In Karanganyar Regency - Husyain Rifai, Muh (CV. Inara, 2020)
Abstract The purpose of this study is to find out about the availability of learning media, including 1) Type, 2) Amount, and 3) Conditions. The research carried out is descriptive research with research data is quantitative data. The study was conducted in 23 high schools in Karanganyar Regency. The population in this study were all high school geography teachers and high school students of class X, XI Social Program and XII Social Program in Karanganyar Regency, which consisted of 17 state high schools and 6 private high schools. The high school which was used as the research subject was determined by proportional random sampling technique to obtain 13 high schools. Futhermore, the samples of teachers and students was determined by purposive sampling, where in each school took 1 teacher respondent and 6 students, so the total sample of teachers was 13 people and students were 78 people. The technique of collecting data in the study uses questionnaire, interview and observation methods. The analysis technique used is descriptive statistical analysis. In summary, from this research found the data condition of geography learning media of high school in Karanganyar Regency in 2016 were obtained, including; 1) The most types of media are Atlas, Pictures, Globe, Maps, Slide Powerpoint, and Computer / Laptop devices, 2) The number of media is classified as medium or available in every media in the school, and 3) The condition of the media is classified as poorly maintained for physical media and is very well maintained for media based on Digital Information Technology.